The Bugis People's Naming System in Bugis Ethnic Tradition - Muhsyanur Muhsyanur (Journal of Language and Literature, 2023)
The naming system in the Bugis ethnic is part of the customary system that has been attached since the Bugis existed. The purpose of this study is to describe the system of naming the Bugis in the Bugis tradition. This research is a type of qualitative research using descriptive methods and ethnographic approaches. Verbal data are in the form of words, phrases, and expressions as well as statements obtained from the interview. The data collected were from three community groups: Tosora in Majauleng District, Lagosi in Pammana District, and Gilireng in Gilireng District. Three community groups are known as cultural villages. They are called cultural villages because these three villages are the source of the history of the Bugis people of South Sulawesi. This study uses an ethnographic approach. This is because research activities are inseparable between the activities of a community group as the object of research and their cultural system. Thus, information or data is obtained from interactions between researchers and the public who are research subjects or data sources. The results of this study are based on findings that show that the Bugis self-naming system is of three types; based on the situation and circumstances, based on natural events, and based on the child’s appearance. The results of this research provide an increase in the revitalization process of traditions that exist in Bugis society. The naming system in the Bugis ethnicity is still being preserved even though advanced technology is growing rapidly.